Political Activism through Liturgical Performance: Teatro Ekyumenikal and the Ecumenical Counterpublic at the United People’s SONA - Crisostomo-Pilario, Junesse D.R. (Philippine Humanities Review; Vol 25 No 1: Philippine Humanities Review (2023-2024): Rebyu ng Arte at Literatura ng Pilipinas, 2025)
While Duterte delivered his fourth State of the Nation Address (SONA) on July 22, 2019, the National Council of Churches in the Philippines (NCCP) Teatro Ekyumenikal also staged a “call to worship” performance during the ecumenical worship gathering before joining the United People’s SONA protest. Through the lenses of performance, embodiment, and counterpublic theory, I ask the question: What does it mean to engage in political activism through liturgical performance? Using ethnographic methods, I examine how this performance integrates various embodied forms, such as Scripture reading, Christian liturgical practices, the aesthetic traditions of Philippine protest theater (or “proletarian theater”), and the performative repertoires of protests and mobilizations whereby marginalized sectors are portrayed as empowered subjects with a voice. The ecumenical liturgical performances in this event aimed to converge with the protest collective and diverge from it by highlighting their Christian identity and the theological dimension of their activism. This ecumenical counterpublic performance not only challenged Duterte’s rhetoric and the dominant conservative Christian stance but also diverged from the secular-political framework of the United People’s SONA, transforming ecumenical practices into politically efficacious acts of ritual through liturgical performance.